2005
DOI: 10.2178/jsl/1120224726
|View full text |Cite
|
Sign up to set email alerts
|

Randomness, relativization and Turing degrees

Abstract: Abstract. We compare various notions of algorithmic randomness. First we consider relativized randomness. A set is n-random if it is Martin-Löf random relative to ∅ (n−1) . We show that a set is 2-random if and only if there is a constant c such that infinitely many initial segments x of the set are c-incompressible: C(x) ≥ |x| − c. The 'only if' direction was obtained independently by Joseph Miller. This characterization can be extended to the case of time-bounded C-complexity.Next we prove some results on lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
134
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 119 publications
(140 citation statements)
references
References 21 publications
4
134
0
2
Order By: Relevance
“…128 Докажите, что В самом деле, априорная вероятность на дереве не меньше меры (и даже любой другой перечислимой снизу полумеры) с точностью до ограниченного множителя, что после логарифмирования и даёт требуемое неравенство.…”
Section: монотонная и априорная сложности и случайностьunclassified
See 1 more Smart Citation
“…128 Докажите, что В самом деле, априорная вероятность на дереве не меньше меры (и даже любой другой перечислимой снизу полумеры) с точностью до ограниченного множителя, что после логарифмирования и даёт требуемое неравенство.…”
Section: монотонная и априорная сложности и случайностьunclassified
“…См. [103,128]; простое доказательство приведено в [9]. Аналогичный критерий 2-случайности можно сформулировать и в терминах префиксной сложности: надо потребовать, чтобы KP (( ) ) было не меньше + KP ( ) − для некоторого и для бесконечно многих ( [197], простое доказательство в [198]).…”
Section: Ks (( ) )unclassified
“…For instance, we have seen that it is impossible for a real to have C(X n) ≥ + n for all n, but Martin-Löf showed in his original paper [101] that there are reals X with C(X n) ≥ + n for infinitely many n, and that these are all 1-random. Joe Miller [103] and later Nies, Stephan and Terwijn [97] showed that such randoms are precisely the 2-randoms, and later Miller [104] showed that the 2-randoms are exactly those that achieve maximal prefix-free complexity (which is n + K(n)) infinitely often. Also Becher and Gregorieff [10] have a kind of index set characterizations of higher notions of randomness.…”
Section: Computability and Randomnessmentioning
confidence: 99%
“…On the other hand, it is possible to show that within the high degrees the separations between computable, Schnorr, and Martin-Löf randomness all occuri ( [97]). In the hyperimmune-free degrees, weak randomness coincides with all of these as well as weak 2-randomness.…”
Section: Computability and Randomnessmentioning
confidence: 99%
“…Nies, Stephan and Terwijn [14] showed that Proposition 2.7 holds if we assume that X is random relative to A.…”
Section: Theorem 23 (Day and Reimann)mentioning
confidence: 99%